Knowledge and attitude regarding insulin therapy among patients treated with insulin for diabetes attending a tertiary care hospital in Sri Lanka - R. A. Higgoda; I. K. Jayasinghe; T. Kannangara (Sri Lanka College of Internal Medicine, 2024)
Introduction: The incidence of diabetes is rising in the South Asian region including Sri Lanka. Insulin is one of the therapeutic options which has a significant impact in optimal control of diabetes but lack of knowledge and negative attitudes among patients pose a significant barrier to proper adherence to insulin therapy. This study aims to assess the knowledge and attitudes towards insulin therapy among patients treated with insulin for diabetes attending National Hospital, Kandy and to assess the association of demographic parameters with knowledge and attitude scores. Methods: An institution-based, descriptive, cross-sectional study was conducted which included 298 randomly selected patients with diabetes who are on insulin attending National Hospital, Kandy. They were assessed with a structured interviewer-administered questionnaire. The data was analysed using SPSS version 22. Results: The knowledge scores of participants were 70%, 26.8% and 3% for good, moderate and inadequate, respectively. The majority (74%) had a favourable attitude towards insulin therapy. The mean knowledge and attitudes scores were 81.9% (95% CI: 79.5% to 84.3%) and 78.3% (95% CI: 73.5% to 83.1%), respectively. Being retired (p= .012) and being on insulin for more than 5 years (p = .028) were associated with a good knowledge score. Conclusions: Majority of the patients with diabetes assessed in the study had good knowledge and a favourable attitude regarding insulin therapy. It is therefore essential to maintain and reinforce the educational and training modalities made available for patients with diabetes.